Between Disciplines and Methods: In Search of an Object of Art Studies at the Academy of Artistic Sciences (1921–1930), Moscow - Silina, Maria (Wiener Slawistischer Almanach, 2026)
This article examines the State Academy of Artistic Sciences (GAKhN, 1921–1930) as an institutional and theoretical project that sought to establish a scientific foundation for art studies through the concept of artistic form. Rather than deriving form from individual artworks, GAKhN scholars constructed a “third object” through the spatialisation of elements, projections across disciplines, and intersections of methods embedded in institutional design. Drawing on archival materials from the Dictionary of Artistic Terms and texts by figures such as Nikolai Brunov, Vasilii Zubov, and Nikolai Zhinkin, the article shows how phenomenology interacted with art-historical materials in the effort to articulate a theory of art. As I argue, despite the strongly spatial and volumetric character of artistic form as a model of inquiry, its most productive legacy lies in a logic of projections and overlaps through which the autonomy of the object of art studies was sought within a materially bounded environment. Although the historical conditions of the GAKhN project can no longer persist as a distinct program, the article situates the Academy as a genealogy of contemporary interdisciplinary art studies and of the enduring institutional tensions that continue to shape the ontology of art today.